German Autumn - Dagerman, Stig, 1923-1954 (Book collections on Project MUSE., 2011)
In late 1946, Stig Dagerman was assigned by the Swedish newspaper Expressen to report on life in Germany immediately after the fall of the Third Reich. First published in Sweden in 1947, German Autumn, a collection of the articles written for that assignment, was unlike any other reporting at the time. While most Allied and foreign journalists spun their writing on the widely held belief that the German people deserved their fate, Dagerman disagreed and reported on the humanness of the men and women ruined by the war-their guilt and suffering. Dagerman was already a prominent writer in Sweden.